Goodness And Beauty In Plato - Riegel, Nicholas (Revista Archai, 2014)
In the first part of this paper I argue that beauty and goodness are at least coextensive for Plato. That means that at least with respect to concrete particulars, everything that is good is beautiful and everything that is beautiful is good. Though the good and the beautiful are coextensive, there is evidence that they are not identical. In the second part of the paper I show significance of this relation. In ethics it implies that the good is the right. It also allows one to see how platonists can believe that goodness exists in mathematics. And it explains the usefulness of mathematics in moral education.